2019
DOI: 10.1051/matecconf/201926601017
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Dredged Sediment as a Replacement for Fine Aggregates in Concrete Mixture: Case Study at Sungai Pekan, Pahang

Abstract: Dredging is essential to maintain suitable depth for shipping by removing dredged sediments from sea and river banks. It is also an important process to supply construction material. In Pahang, increasing flood cases is occurring due to increased sea and river bed level. Thus, dredging is needed to be performed in this location. In addition, the rapid growth of the construction industry requires a sustainable approach. The reuse of dredged sediments as construction material could be a sustainable approach. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The lowland and swamp area in the town of Pekan is easily flooded when heavy rains cause water spillover from the Pahang River. Hence, communities in Pekan were the most affected among the surrounding districts during the massive flood in the year 2014 [31]. It is reported that Pekan has the highest numbers of victims compared with the other six districts that were flooded (Temerloh, Maran, Kuantan, Bera, and Jerantut), with a total of 11,154 people affected, and an estimated value of RM58 million for basic infrastructure and individual damage [4,28].…”
Section: Study Areamentioning
confidence: 99%
“…The lowland and swamp area in the town of Pekan is easily flooded when heavy rains cause water spillover from the Pahang River. Hence, communities in Pekan were the most affected among the surrounding districts during the massive flood in the year 2014 [31]. It is reported that Pekan has the highest numbers of victims compared with the other six districts that were flooded (Temerloh, Maran, Kuantan, Bera, and Jerantut), with a total of 11,154 people affected, and an estimated value of RM58 million for basic infrastructure and individual damage [4,28].…”
Section: Study Areamentioning
confidence: 99%